(untitled) (Studia Prawnicze / The Legal Studies, 1971)
Autor porusza kwestie dotyczące obowiązywania umów międzynarodowych na terytoriach nowopowstałych państw w związku z likwidacją kolonializmu. Autor opisuje wpływ odzyskania niepodległości na umowy powstałe przed ustanowieniem protektoratu oraz w trakcie jego trwania. Omawia sytuacje prawną w państwach, które były pod protektoratem Francji tj. (Maroko, Tunezji, Indochiny) oraz Wielkiej Brytanii tj. (Federacji Malajskiej i Ugandy). Ponadto autor przedstawia swoje rozważania dotyczące charakteru prawnego układów (bądź klauzul) o przejściu praw i zobowiązań traktatowych, które są istotne dla doktryny prawa międzynarodowego. The author addresses issues concerning the validity of international agreements in the territories of newly created states in connection with the dismantling of colonialism. The impact of independence on agreements created before and during the establishment of the protectorate is described. Legal situation in countries that were under the protectorate of France i.e. (Morocco, Tunisia, Indochina) and the UK (Malay Federation and Uganda) is described. Moreover, the author presents his considerations on the legal nature of agreements (or clauses) on the transfer of treaty rights and obligations which are relevant to the doctrine of international law.